A scoping review of nursing education for firearm safety. (February 2023) - Drake, Stacy A.; McDaniel, Mary; Pepper, Catherine
Abstract: Background: Firearm violence, whether intentional or accidental, affects families worldwide. Nurses often encounter firearm-related injury and death with little knowledge or preparation for dealing with firearm safety issues. Objectives: The aim was to locate published research on nurse education in firearm safety and examine the preparation of nurses to deal with issues of firearm safety as a deterrent toward decreasing violence. The review included nurse perceptions of barriers and facilitators related to firearm safety in clinical situations. Design: A literature scoping review for article identification, examination, and reporting was structured on the extended form of Arksey and O'Malley's 5-step design framework. Data sources: Databases CINAHL, MEDLINE, Sociological Abstracts, PsychInfo, and ERIC were searched for articles in English language published between 2010 and 2021 that included nurses in the studies' samples. Review methods: Searches were managed via Covidence®, a literature screening and data extraction tool. Two independent reviewers screened the articles retrieved from the databases by title, abstract, and full-text review. Data from selected articles were extracted onto a spreadsheet and critically appraised for eligibility. Results: A search of healthcare databases resulted in identification of 645 articles, of which 15 met inclusion criteria. Seven of the 15 articles addressed nurse firearm safety preparation, and seven related to counseling firearm safety for suicide prevention. Main barriers included lack of standardized guidelines, inadequate knowledge, and discomfort discussing firearm safety with patients and families. Conclusions: The scoping review findings show a noticeable gap: nurse education addressing firearm safety is, for all purposes, non-existent. A need exists for evidence-based training within academic curricula and across acute and behavioral healthcare settings. Highlights: Nursing education addressing firearm safety is, for all purposes, non-existent. Absence of education and resources adversely affect nurses' ability to address firearm safety. Multi-level solutions are offered.